Checklists in action in neonatal medicine: improving breastfeeding rates. Issue 6 (June 2019) - Parish, Abby; Doherty, Cora
Abstract: Checklists were initially used within the aviation industry before being extrapolated into a number of other industries and arriving much later to medicine, where they are used as tools to improve patient safety. Checklists improve reliability, reduce variation and standardise care, ensuring that staff can review their tasks and confirm compliance before moving on to the next step. They have flexibility in application and are used in both within the acute care setting, in addition to service planning and delivery. This article outlines the successful development and implementation of the Cardiff Breastfeeding Checklist into clinical care on a tertiary neonatal unit supporting a quality improvement initiative. Features of a 'good' checklist are highlighted and how it forms the framework for the Model for Improvement and involves both parents and the staff team. The results show a sustained three-fold improvement in breastfeeding rates on discharge. The checklist approach can be used to ensure that simple standards are applied for every patient, every time, motivating staff and improving patient safety.